(untitled) (Revista Educação, Artes e Inclusão, 2025)
The main objective of this research is to propose reflections on the University Theater Group (GTU/UFPA) as an extension project and its creative path of theatrical performance in the city of Belém/PA. To do this, the UFPA School of Theatre and Dance is contextualized, the locus where the group arose and to which it returns; the path of the University Theatre Group is highlighted through its creation from the Novos Encenadores extension project developed by Charone (2018) and the role of this group in the dialogue with Theatre and Education is understood. This article was written as a finalization of the Postgraduate in Languages and Arts in Teacher Training (LAFD/IFPA), in the research line of creative processes, aesthetic and cultural knowledge of languages. The theoretical framework includes the definitions of staging, university theater, theater-education and creative processes, covering, respectively, the ideas of Koudela (2008), Carreira (2012), Antonello (2017) and Canda (2020). The methodological approach of this work consisted of a qualitative case study of a descriptive nature, based on experience reports, with memory and documentary consultation as data collection tools, through interviews on the subject with four subjects divided into four categories in this context: the teacher who conceived the GTU/UFPA, a student from the school of theater and dance, an external participant in the group and a new director. The main focus of the interviews was the importance of the GTU/UFPA and each participant’s perceptions of this group. From the collection/survey/analysis of this data, it was possible to see that this group, during its period of operation, had a direct relationship with education and creative processes, since it returned to the university as an extension project, proposed various forms of staging, stimulated creation at a collective level and made it possible to put on several shows. In this way, it was possible to highlight the impact of the GTU/UFPA as a creative path for theatrical performance in the city of Belém/PA.